Conceptual data management and communication for smart distribution system - Jamian, J.J.; Mustafa, M.W.; Mokhlis, Hazlie; Bahamdin, M.A. (IEEE, 2011)
Load adjustment is a new concept in smart grid system that can be used to balance the frequency of the system by adjusting their power consumption. However, the system required to have effective data communication management. The introduction of Smart Home System (which consists of Smart Appliance (SA) and Smart Meter (SMÂ», Smart Regional Server (SRS) and Smart Server (SS) as well as the messaging sequence between these entities will be used to manage data communication in smart distribution system. The communications between these devices will be via Power Line Communication (PLC) and WiMAX as a medium to transfer the data to the SRS. Transport Control Protocol (TCP) will increase the reliability of transferring data. By using the propose communication and data management technique, the use of load-balancing control to recover the frequency in a smart distribution grid system will be achieved.